Towards the use of asteroseismology to investigate the nature of dark matter - Lopes, Ilidio (2012)
The annihilation of huge quantities of captured dark matter (DM) particles inside low-mass stars has been shown to change some of the stellar properties, such as the star's effective temperature or the way the energy is transported throughout the star. While in the classical picture, without DM, a star of 1 Msun is expected to have a radiative interior during the main sequence, the same star evolving in a halo of DM with a density ρχ > 108 GeV cm-3 will develop a convective core in order to evacuate the energy from DM annihilation in a more efficient way. This convective core leaves a discontinuity in the density and sound-speed profiles that can be detected by the analysis of the stellar oscillations. In this paper we present an approach towards the use of asteroseismology to detect the signature produced by the presence of DM inside a star, and we propose a new methodology to infer the properties of a DM halo from the stellar oscillations (such as the product of the DM density and the DM particle-nucleon scattering cross-section).